ANALYSIS OF KEY RISK FACTORS IN THE YOUTH INFORMATION ENVIRONMENT (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article aims to examine and classify the key risk factors affecting the youth information environment. It explores how various forms of digital content and interaction impact the psychological and social development of young users. The study investigates the prevalence and effects of harmful online phenomena such as misinformation, cyberbullying, data breaches, and exposure to extremist ideologies. By employing a mixed-methods approach—combining surveys, content analysis, and expert interviews, the research seeks to provide a comprehensive understanding of these risks.